2013
DOI: 10.1037/a0032761
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depressive symptoms predict adolescent healthcare utilization and charges in youth with Type 1 diabetes (T1D).

Abstract: Maternal depressive symptoms are an independent predictor of health care utilization and charges in adolescents with Type 1 diabetes. Interventions aimed at identifying and treating depressive symptoms in mothers could not only enhance caregiver quality of life but could also be economically advantageous for payers and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…There were no significant differences concerning the mothers' assessment of their child's HRQOL in the intervention group versus the control group. Earlier studies show that mothers often tend to be over-involved and internalize psychological aspects of their child's disease [30]. This fact might be reflected in our results.…”
Section: Discussionsupporting
confidence: 65%
“…There were no significant differences concerning the mothers' assessment of their child's HRQOL in the intervention group versus the control group. Earlier studies show that mothers often tend to be over-involved and internalize psychological aspects of their child's disease [30]. This fact might be reflected in our results.…”
Section: Discussionsupporting
confidence: 65%
“…High levels of depression in mothers of children with T1DM may lead to difficulties in paying attention to the medical care of their children. A study by Clayton et al [20] has shown that adolescents of mothers with high depressive symptoms were twice as likely to have an emergency room visit and 3 times as likely to be hospitalized. It is clear that people who suffer from both diabetes and depression have poorer metabolic control [8].…”
Section: Discussion ▼mentioning
confidence: 99%
“…Most studies examining psychosocial problems in youth with type 1 diabetes (T1D) have focused on rates of depressive symptoms [10], the negative impact of depressive symptoms on health outcomes including glycemic control [11, 12••], and the impact of self-reported and maternal depressive symptoms on hospitalizations in youth with T1D [13,14]. Fewer studies have specifically examined the occurrence of anxiety in individuals with T1D diabetes, and those that have primarily focused on fear of hypoglycemia (FOH) and needles.…”
Section: Introductionmentioning
confidence: 99%